Modulation of plasma membrane Ca2-ATPase by neutral Phospholipids: effect of the micelle-vesicle transition and the bilayer thickness - Pignataro, María Florencia (2015)
Background: Membrane proteins require phospholipids to be biologically active. Results: An increase of phosphatidylcholine/detergent molar ratio leads to a biphasic behavior of the PMCA Ca2-ATPase activity, whose maximum depends on phosphatidylcholine characteristics. Conclusion: The optimum hydrophobic thickness for PMCA structure and Ca2-ATPase activity is about 24 Å. Significance: Differential modulation by neutral phospholipids could be a general mechanism for regulating membrane protein function.